Impact of Cyber-Security on Fraud Prevention in Nigerian Commercial Banks - Chika Odukwu Victory; Eke Promise; Chukwumati N Mike (Penerbit Goodwood, 2022)
Purpose: The purpose of this research was to investigate the impact of cyber-security on fraud prevention in Nigerian commercial banks. Method: The researcher collected primary data through the interview (WhatsApp video call) conducted with the senior employees of the respective commercial banks who know the subject matter. Result: The outcomes of the research demonstrated that cloud security statistically increases fraud prevention in Nigeria; also, that application security statistically increases fraud prevention in Nigeria. Contributions: it was suggested that Nigerian financial industry should be able to effectively detect fraudulent transactions and prevent them from causing financial or reputational damage to the customers or other financial institutions (FI), also, there should be a special awareness program to educate the public on how to always use strong passwords for their devices to prevent hacking, loss of money, or other resources. Novelties: The variables adopted in this study as well as the sample size, results, and recommendations have not been used by eminent scholars in this manner. Limitations: the results of this study would be limited to commercial banks in Nigeria, and therefore may not apply to other sectors of the economy. Similar studies were suggested to be carried out, covering other sectors of the economy to validate these results.